Generational Accounting and Hungarian Pension Reform - Gál, Róbert I. (World Bank, Washington, DC, 2014)
The essence of generational accounting is to break down total net contributions in a given year to each cohort and to project this profile into the future. Using additional assumptions on the discount rate and the growth of productivity and population, the per capita net contribution of future generations can be determined, which satisfies the inter-temporal budget constraint. Generational accounts in the Hungarian pension system show that the 1997 reform package significantly reduced the financial tension generated by demographic and institutional factors.